Perspectives of clinicians on the potential impact of social media on social and emotional wellbeing, training needs, and screening recommendations: a preliminary examination - Domoff, Sarah E.; Armstrong, Stacey B.; Rollings, Heide; Mancuso, Amy; Janney, Carol A. (Frontiers in Psychiatry, 2025)
IntroductionSocial media is integral to adolescents’ lives, with the separation between adolescents’ online and offline worlds harder to distinguish. Adolescent development occurs online via the opportunity to connect with others and explore themselves. Despite the potential for benefits, some adolescents with underlying mental health conditions are at risk for stressful online experiences, such as cyberbullying. The complexity of the impact of social media on adolescents necessitates an understanding of mental health providers’ perspectives on their observations of youth treated, how they support youth in navigating social media, and suggestions for clinical and research priorities to address barriers encountered in developing resilient and prosocial interactions online. The purpose of this qualitative study was to understand these perspectives in stakeholders across mental health-related disciplines.MethodsIn Fall 2022 to Spring 2023, 14 participants were interviewed regarding their perspectives on social media and mental health, how they screen for harmful experiences online, and their approach to supporting youth who have experienced online stressors. We used an inductive thematic analysis to identify themes.ResultsThemes reflected clinicians’ perceptions of positive and negative impacts of social media on youth; how they communicate with youth about their experiences; preferences or recommendations for screening for harmful experiences; and barriers encountered in addressing use and impacts.DiscussionWe outline recommendations for implementing screening for social media experiences, responding to harmful online experiences, and future clinical research directions to fill gaps in training and service provision related to adolescents’ social media use.